Efficacy of Omentum-Preserving Gastrectomy for Patients With Gastric Cancer: A Systematic Review and Meta-Analysis - Li, Zonglin; Song, Min; Zhou, Yejiang; Jiang, Huaiwu; Xu, Linxia; Hu, Zhengchuan; Liu, Yi; Jiang, Yifan; Li, Xin (Frontiers in Oncology, 2021)
Background Complete omentectomy is considered to be essential in the radical gastrectomy for gastric cancer (GC), but its clinical benefit remains unclear. This study aims to evaluate the efficacy of omentum-preserving gastrectomy (OPG) for patients with GC. Methods Studies comparing the surgical and oncological outcomes of OPG and gastrectomy with complete omentectomy (GCO) for GC up to March 2021 were systematically searched from PubMed, Web of Science, Embase, and Cochrane Library. A pooled analysis was performed for the available data regarding the baseline features, surgical and oncological outcomes. The RevMan 5.3 software was used to perform the statistical analysis. Quality evaluation and publication bias were also conducted. Results Nine studies with a total of 3335 patients (1372 in the OPG group and 1963 in the GCO group) undergoing gastrectomy were included. In the pooled analysis, the baseline data in two groups were all comparable (p > 0.05). However, the OPG group was associated with shorter operative time (MD = −18.67, 95% CI = −31.42 to −5.91, P = 0.004) and less intraoperative blood loss (MD = −38.09, 95% CI = −53.78 to −22.41, P < 0.00001) than the GCO group. However, the number of dissected lymph nodes (MD = 2.16, 95% CI = −0.61 to 4.93, P = 0.13), postoperative complications (OR = 0.92, 95% CI = 0.74 to 1.15, p = 0.47), overall recurrence rate (OR = 0.83, 95% CI = 0.66 to 1.06, p = 0.14), peritoneal recurrence rate (OR = 0.91, 95% CI = 0.65 to 1.29, p = 0.60), 3-year relapse-free survival (RFS) rate (OR = 1.40, 95% CI = 0.86 to 2.27, p = 0.18), and 5-year RFS rate (OR = 1.21, 95% CI = 0.95 to 1.55, p = 0.12) of the two groups were comparable. Conclusions OPG might be an oncologically safe procedure with better surgical outcomes for patients with GC than GCO. However, high-quality randomized controlled trials are needed to confirm this benefit.